(untitled) (Cadernos de Sociomuseologia, 2010)
The ideas on which this paper is based are drawn from my thesis “Interactivity in Museums. A Relationship Building Perspective” written in 2007 for the fulfillment of the Master Degree in Museology at the Reinwardt Academy in Amsterdam. The main arguments are that the notion of Interactivity conceptualized within a technological orientation coupled with the pedagogic approach of mere information transmission need to be reconsidered; that Interactivity in museums is a conception both misinterpreted and under-implemented; and that the problems of understanding Interactivity will resolve by identifying the aspects which define Interactivity and most importantly focus on why they matter in a broader socio-cultural context within museums. Without an intention to attribute all the developments and advances associated with new museological practice, in some deterministic way, solely to politics and economic change, I argue that the new strategies adopted by museums towards progression and broader accessibility –at least regarding interactivity, seem to be linked more with a dominant commercialization of culture and education, than with a belief towards an effect on social change through the promotion of social interaction within a pluralistic and multicultural society, acknowledging the diversity of nature, opinion and practices, which can be combined instead of contrasting each other.